(untitled) (Journal of Environmental Science Studies, 2023)
During floods, driftwood is generated simultaneously with sediment runoff, may impinge and accumulate on bridge piers. In this case, the water level rises upstream of the bridge, flooding from the river, resulting in major damage, such as overtopping and collapse of houses and bridges. Further, a high velocity flow passing over the pier due to impact of the flow at the upstream face of the pier causes scouring of the river bottom around the pier. In this study, the installation of consecutively assembled boulders was proposed in order to protect against scouring around the pier. A trapezoidal elliptical shape pier was also proposed as a countermeasure to reduce driftwoods capturing. As a comparative study, revetment blocks, which are conventionally used as countermeasure works, were installed. The experimental results revealed that the proposed structure was effective in reducing driftwood deposition and preventing gravel bed scouring, based on analysis using flow velocity with time series variation, vector diagrams, and driftwood model.